On the value of comparative physiology - Sweazea, Karen L. (Henry Stewart Talks, 2016)
Adaptations: exploration of various definitions, Reasons for variations in animals, Natural Selection, Biomimicry: nature-inspired solutions, Top 10 causes of morbidity and mortality in humans, What is a model – focus on the natural phenomena, Animals resistant to heart disease or cancer, Hypoxia and anoxia tolerant species, Biomimicry for injury prevention and treatment, Animal models of: neurodegenerative diseases, diabetes, kidney function, Biomimicry to prevent disease transmission, Understanding stress in animals